Marooned Plants: Vernacular Naming Practices in the Mascarene Islands. (1st February 2015) - Kull, Christian A.; Alpers, Edward A.; Tassin, Jacques
Abstract : This article explores possible histories of plant exchanges and plant naming tied to the slave trade between East Africa, Madagascar and the Mascarene Islands. The subsequent ' marronnage ' of slaves on these islands - their escape from captivity, sometimes to live in mountain hideouts - continues to inspire cultural references. Inspired by the use of the adjective ' marron/marronne ' for a number of plants on Reunion Island, we compile evidence of plant exchanges and plant naming from ecological records, historical accounts and the use of descriptive, emotive or symbolic vernacular names as clues for deepening our knowledge of historical societies and environments. The evidence from the Mascarenes opens a window into the role of the African diaspora in plant introduction, diffusion, domestication and cultivation. We document that maroons relied on a variety of wild, escaped and cultivated plants for their subsistence. We also highlight the role of marronnage in the popular and literary imaginary, with the result that many plants are named ' marron/marrone ' in a metaphorical sense. Finally, we identify a few plants that may have been transported, cultivated, or encouraged in one way or another by maroons. Along the way, we reflect on the pitfalls and opportunities of such interdisciplinary work.